Ammonium and potassium effects on carrot response to water deficit - Ayman M.S. Elshamly; Saudi A. Rekaby; A.S. Abaza; Kassem A.S. Mohammed; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal; Maximilian Lackner (Agricultural Water Management)
For a comprehensive understanding of carrot drought tolerance, studying nutrient homeostasis alongside physiochemical modifications, especially under different drought intensities and nutrient supplements is essential. In this work, the effect of soil ammonium nitrate and foliar potassium humate applications in different combinations and rates on nutrient concentrations, agronomic traits, and irrigation water use efficiency was investigated. Three deficit water levels in the field in southern of Egypt were used, namely well-watered irrigation level, continuous mild deficit level, and moderate deficit level. The current work was organized in a split-plot with three replicates. Adopting the mild deficit level and applying 250 kg ha−1 ammonium nitrate combined with 200 g 100 L−1 potassium humate yielded beneficial impacts that relieved carrot plants stress and lead to enhanced irrigation water use efficiency. Adopting this approach in the short mild deficit term increased leaf concentrations of K (+29 %), Mg (+45 %), Na (+24 %), and Zn (+12 %) and decreased leaf concentrations of N (-10 %), P (-13)%, Fe (-18 %), Mn (-21 %), and Cu (-25 %) compared to well-watered conditions, while in the long mild deficit term, the leaf concentrations of P (+25 %), K (+44 %), Ca (+11 %), Mg (+21 %), Na (+8 %), and Cu (+7 %) increased and leaf concentrations of N (-8 %), Fe (-12 %), and Mn (-30 %) decreased compared to well-watered irrigation. The adaptive responses in nutrient homeostasis improve carrot resilience to deficit stress and allow plants to maintain their developing processes and water use. Interestingly, when the potassium humate rate was increased up to 400 g 100 L−1 and applied in a combination with 250 kg N ha−1 under the well-watered level, negative impacts were observed on water use of carrots which decreased by 52 % and 33 % compared to mild and moderate deficit, respectively.